THE EFFECT OF PANCASILA INDUSTRIAL RELATIONS ON EMPLOYEE PERFORMANCE (Case Study At PT Garam (Persero), Sumenep Office, Indonesia) - Wanda Gema Prasadio Akbar Hidayat (SEAN Institute, 2023)
Employee performance is crucial in determining the success of company management and development. The employee performance level can be determined by analyzing the quantity of work, quality of work, job knowledge, creativeness, cooperation, dependability, initiative, and personal quality. This study aims to determine the effect of Pancasila industrial relations on employee performance. Descriptive research with causality method study was performed. We evaluated industrial relations variables based on the Godhead, justice and civilization, Indonesian unity, wisdom and social justice. These variables had significant positive effect on employee performance. The industrial relations and employee performance level at PT. Garam (Persero) Indonesia increased.